Improving students' writing performance through the use of grammar checker - Jayavalan, Kalpana; Mohamed Razali, Abu Bakar (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
Writing is a complex process, recursive rather than linear in nature, involving thinking, planning, discovering what to say, drafting and re- drafting. Learning to use the correct mechanical and grammatical forms of written language is a slow, developmental process, unique to each student and does not progress in a similar pattern. For years, students learn to write correctly by writing, revising and proofreading their own work with help from the teacher. However, in the last two decades, a number of software programs have appeared to be able to improve students writing, including grammar and punctuation. The rapid progress of computer technologies creates a plethora of ways in which technology can be integrated into one of the alternatives to facilitate writing instruction, particularly on grammar checking, especially with the application of grammar checkers. Educational software, such as the grammar checker, is one of the most important tools in computer-aided education, especially in teaching writing. These are the “software prepared in computer environment and intended for shortening the teaching process making the topic more visual and audible by taking advantage of computer environment in teaching a certain topic” (Kazu & Yavuzalp, 2008, p. 113). This conceptual paper analyses a number of relevant studies that were done on the use of grammar checkers in writing. The authors also discusses on grammar checkers used in Malaysia and its potentials in essay writing.